The role of health behaviors and food insecurity in predicting fruit and vegetable intake in low-income children. Issue 2 (3rd April 2017) - Canter, Kimberly S.; Roberts, Michael C.; Davis, Ann M.
ABSTRACT: Research supports the importance of adequate fruit and vegetable intake during childhood. The current study examines relationships between physical activity, sedentary behavior, sleep, food insecurity, and fruit and vegetable intake in a sample of low-income, elementary-aged children. 148 participants were recruited from several agencies serving low-income families in a large midwestern metropolitan area. A measurement model was specified to ensure good fit between the data and predictive model. A structural model was run and several significant findings emerged. Food insecurity significantly predicted vegetable intake (latent regression coefficient = −0.18, p < 0.05), such that children with higher food insecurity consumed fewer servings of vegetables. Physical activity also significantly predicted fruit intake (latent regression coefficient = 0.32, p < 0.01) and vegetable intake (latent regression coefficient = 0.26, p < 0.01), such that children who were more physically active consumed more servings of fruits and vegetables. Data indicate that children with high food insecurity consumed fewer vegetables, and that physical activity is significantly related to fruit and vegetable intake. Possible implications for public policy are discussed.